On Refugee Agency, Bio-Politics, and a New World - Abushama, Hashem (Refuge: Canada's Journal on Refugees, 2021)
This short intervention starts by discussing Giorgio Agamben’s theoretical formulation of ‘bare life,’ popular in refugee studies. Thinking with the case study of Palestinian refugee camps, particularly in the West Bank, it argues that there are clear limitations to the discourse of and bare life. I argue that ‘bare life’ neither accounts for the multilayered relations of power, particularly colonialism, slavery, and indigenous genocide, that systemically make certain populations more susceptible to its power than others. Nor does it account for the modes of of those who are systemically relegated to its sphere. I conclude by working through some of the theoretical formulations around body politics from the field of Black studies, particularly Alexander Weheliye's 2014 concept of the flesh, in order to explore new directions they may point us towards in refugee studies.